Evaluation of protection by COVID-19 vaccines after deployment in low and lower-middle income countries. (January 2022) - Clemens, John; Aziz, Asma Binte; Tadesse, Birkneh Tilahun; Kang, Sophie; Marks, Florian; Kim, Jerome
Summary: The availability and use of vaccines for the coronavirus disease 2019 (COVID-19) in low and middle-income countries (L/MICs) lags far behind more affluent countries, and vaccines currently used in L/MICs are predominantly of lower efficacy. As vaccines continue to be rolled out in L/MICs, successful control of COVID-19 by vaccines requires monitoring both of vaccine protection of vaccinees (effectiveness) and of the entire targeted populations, including vaccine herd protection of non-vaccinees (impact). To be of greatest relevance to L/MICs, there is the need to address the distinctive medical and demographic features of populations, health systems, and demography that may greatly affect vaccine performance in these settings. We identified 58 published studies that included 85 evaluations of the effectiveness of different COVID-19 vaccines globally. Only three were done in L/MICs, and no impact studies were identified in these settings. Post-deployment studies of the protection by COVID-19 vaccines rolled out in L/MICs constitute an important but currently neglected global priority.